MedPhoto Festival: The case of a socially engaged lens-based artistic initiative at the southernmost edge of Europe - Kechris, Dimitris (Design/Arts/Culture, 2024)
In 2016, during the escalation of the refugee/immigration crisis, an international lens-based festival named MedPhoto was initiated in Greece by a small grassroots collective in cooperation with the Contemporary Art Museum of Crete. MedPhoto derived from an encounter of people coming from diverse disciplines (photographers, activists, graphic designers, curators, journalists and scholars), whose objective has been to establish a socially engaged cultural community. Having Crete as its point of departure (since this island constitutes an emblematic crossroad of various civilisations and a pivotal geopolitical site in the history of the Mediterranean), MedPhoto has been developing a wide range of activities across Greece, such as exhibitions, educational workshops, open discussions and publications, all of them explicitly oriented towards the cultivation of a radical dialogue on urgent contemporary issues. It is this ongoing endeavour that the present article briefly reflects on, pointing to some of the most noteworthy events MedPhoto realised and emphasising particularly its latest exhibition which addressed the endangered notion of democracy.